Resolving Land Sale Disputes through Legal Advocacy: A Normative Study of Judicial Reasoning in Plural Legal Systems - M. Yazid Fathoni; Diangsa Wagian; Lalu Hadi Adha (Universitas Negeri Semarang, 2025)
The transfer of land rights is a classic problem, but the legal basis that validates its validity remains ambiguous to date. Although Government Regulation Number 24 of 1997 concerning Land Registration emphasizes that the transfer of land rights is executed using a PPAT deed, judges sometimes have varying legal considerations when deciding the issue of the validity of the transfer of land rights. The validation of these considerations is sometimes also based on the Burgerlijk Wetboek, or sometimes based on Customary/Adat Law. Based on the Morality-Positivism theory, this article will explore how judges should decide a case that falls into the category of